Racial Differences in the Association of Fruit and Vegetable Intake With Cognitive Decline. (14th June 2022) - Agarwal, Puja; Beck, Todd; Dhana, Klodian; Liu, Xiaoran; Rajan, Kumar; Tangney, Christy; Zhang, Yanyu; Barnes, Lisa
Abstract: Objectives: Diet has been shown to be related to slower cognitive decline but there is limited knowledge on whether this relationship varies across race. Given the higher risk of cognitive impairment among African Americans (AA), diet could be a modifiable risk factor in this population. In this study, we examined racial differences (AA vs others) in the association of fruit (total fruits; berries) and vegetable (total vegetables; green leafy) intake with cognitive decline. Methods: Analyses included 5423 participants of the Chicago Health and Aging Project (62% African American, 63% women, age = 73.6 (±6.1) years, education = 12.5 (±3.5) years) who completed a food frequency questionnaire and had at least two cognitive assessments (for each, a composite of 4 cognitive tests) for an average follow-up of 7.8 (±4.6) years. We used mixed models adjusted for age, sex, education, race, cognitive activities, physical activity, and total calories. Subsequent models tested interactions of diet (fruits and vegetables) with race, and models were race-stratified if p for interaction ≤0.05. Results: Compared to NHW, AA had a lower (p < 0.0001) intake of total fruits, berries, and vegetables but a similar green leafy intake (p = 0.94). At baseline those in the highest quintile of vegetable (β = 0.126, p < 0.0001) and green leafy (β = 0.094, p = 0.0001) intake had better cognitive scores compared to those at the lowest quintile. During follow-up, vegetable intake in the overall population was associated with slower cognitive decline (Q5(4 servings/day) vs. Q1(<1 serving day) = β = 0.011, p = 0.02) and the association for green leafy intake (>1 serving/day vs. once/week) showed a trend (p = 0.08). There were no racial differences in the associations for vegetable and green leafy intake, however, the berry * race interaction was significant (p = 0.05). In stratified models, berry (≥once a week vs. less: β = 0.016, p = 0.01) intake was related to slower cognitive decline, but only in AA. Fruit intake was not associated with cognitive decline in either group. Conclusions: Vegetable and green leafy intake may slow cognitive decline in older adults. Increasing berry intake may be an important public health intervention for brain health, particularly among African Americans. Funding Sources: Alzheimer's Association and NIA.